Simulasi Pengunaan Dongeng “Bubu dan Biji Ajaib” kepada Petugas Lapangan Terkait Kepatuhan Minum Obat pada Anak dengan HIV/AIDS - Sri Handayani; Rifda Wahyuni; Gusliani Eka Putri (CV. CENDIKIA JENIUS INDONESIA, 2025)
The incidence of HIV/AIDS in children continues to rise, mainly due to mother-to-child transmission. Although antiretroviral (ARV) therapy effectively reduces mortality, adherence among children remains low. This community service activity aimed to improve field officers’ pedagogical skills in educating children on ARV adherence through storytelling. The activity was conducted on June 12, 2025, at Yayasan Akbar in Padang City, involving 10 field officers. The method included training on storytelling techniques using the book